2019
DOI: 10.1109/twc.2018.2890061
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Multi-Dimensional Mapping of Higher Order Modulations for BICM-ID Over Rayleigh Fading Channels

Abstract: Multi-dimensional (MD) mapping offers more flexibility in mapping design for bit-interleaved coded modulation with iterative decoding (BICM-ID) and potentially improves the bandwidth efficiency. However, for higher order signal constellations, finding suitable MD mappings is a very complicated task due to the large number of possible mappings. In this paper, a novel mapping method is introduced to construct efficient MD mappings to improve the error performance of BICM-ID over Rayleigh fading channels. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is impossible for regular BICM, which has become a standard for the current wireless systems, due to the gray labeling map used therein. In recent years, BICM-ID had many variations, like bitinterleaved space-time coded modulation with iterative decoding [8], BICM-ID exploiting signal space diversity [9], bit-interleaved polar coded modulation with iterative decoding [10], or BICM-ID with multidimensional labeling [11,12].…”
Section: Bicm-id Essentialsmentioning
confidence: 99%
“…It is impossible for regular BICM, which has become a standard for the current wireless systems, due to the gray labeling map used therein. In recent years, BICM-ID had many variations, like bitinterleaved space-time coded modulation with iterative decoding [8], BICM-ID exploiting signal space diversity [9], bit-interleaved polar coded modulation with iterative decoding [10], or BICM-ID with multidimensional labeling [11,12].…”
Section: Bicm-id Essentialsmentioning
confidence: 99%
“…Gray labeling, which is widely used in current wireless systems that employ original BICM, such as WLAN [ 1 , 2 ] and digital terrestrial television broadcasting [ 3 , 4 ], has been shown to be the worst choice from the perspective of iterative decoding goals. The optimal labeling maps for BICM-ID have been investigated in many papers, e.g., [ 5 , 6 , 7 ]. The most popular optimization target for labeling involves maximizing the asymptotic coding gain while maintaining the energy per bit to noise power density ratio at infinity.…”
Section: Introductionmentioning
confidence: 99%
“…The works [ 9 , 10 ] proposed a design method for quasi-Gray labeling based on the edge-profile. The other newer related works about the labeling focus on the BICM-iterative decoding (ID) [ 11 , 12 , 13 , 14 ] or the other constellation [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%